Pengaruh Electronic Word Of Mouth Terhadap Minat Berkunjung Dengan Mediasi Theory Of Planned Behavior Pada Obyek Wisata Halal Di Kabupaten Jombang - Purwanto, Nuri; Rofiah , Chusnul (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
This study aims to determine the effect of the effect of electronic word of mouth on halal travel interest mediated by Theory of planned behavior (TPB). The research method uses quantitative by using explanatory research types. The population in this study were all visitors of religious tourism in Jombang Regency who learned information about these religious tourism from social media. While the sampling technique is purposive random sampling where sampling from the population is carried out randomly and with certain considerations by taking a number of 332 respondents, research results show that ewom influences the dimensions of Theory Planned Behavior namely subjective norm, attitude and Percected behavior control, as well as subjective norms and attitudes directly affect inttention to travel, ewom indirectly influences inttention to travel through atttitude and perceived behavior control